2020
DOI: 10.3233/ch-190594
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lymphocyte subpopulations and cardiovascular markers in pericardial fluid of cardiac surgery patients

Abstract: BACKGROUND: Composition of pericardial fluid (PF) may reveal immunological processes influencing oxidative stress and microcirculation of different tissues of the heart and may play a role in the course of myocardial infarction, atherosclerosis, and aortic stenosis. PATIENTS AND METHODS:We investigated lymphocyte populations, cardiovascular markers and immunoglobulin composition in PF and blood samples of patients undergoing CABG operation and compared them to those who had aortic valve surgery. RESULTS:The am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…However, Liu and colleagues reported higher levels of INF-α in pericardial effusions in patients with pericarditis [ 23 ]. In relation to adhesion molecules, only P-selectin levels were previously studied with similar findings to our present study (higher in serum than in pericardial fluid) [ 18 ]. From one side, the molecular weight and structure of the proteins determine their ability to diffuse from the cardiac interstitial space into the pericardial sac via the visceral epicardial layer [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, Liu and colleagues reported higher levels of INF-α in pericardial effusions in patients with pericarditis [ 23 ]. In relation to adhesion molecules, only P-selectin levels were previously studied with similar findings to our present study (higher in serum than in pericardial fluid) [ 18 ]. From one side, the molecular weight and structure of the proteins determine their ability to diffuse from the cardiac interstitial space into the pericardial sac via the visceral epicardial layer [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…In fact, in our study, the cellular population of the pericardial fluid was characterized by the abundance of macrophages and mesothelial cells. This hypothesis is supported by the finding that epicardial mesothelial cells under normal conditions are able to synthesize IL-6 [ 12 ] while the T lymphocytes present in the pericardial fluid are capable of synthesizing IL-6, IL-10, and INF-γ [ 18 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our results showed that when cells were stimulated with phytohemagglutinin, the percentage of Tlymphocyte subpopulations was decreased (Figure 4), which occurred regardless of treatment. This finding is not new since Fock, et al (2010) had already reported this phenomenon, which was later confirmed by Gilicze, et al (2019), who attributed it to the loss of expression of the surface marker CD3 due to activation of the Apoptotic mechanisms of lymphocytes caused by stimulation with phytohemagglutinin.…”
Section: Various Modulatory Effects Have Been Reportedmentioning
confidence: 76%